Profile of Implementing Google Classroom As A SMK Physics Learning Media - Intan Fatmawati; Dwi Sulisworo (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2021)
Learning management system (LMS) is a learning solution in the midst of the Covid-19 pandemic situation. In addition, the LMS learning media is also a medium that supports education in the demands of technological development 4.0. LMS is an online-based application designed to assist the learning process with creative and innovative material designs. LMS has many types, this time the researcher uses google classroom as a learning medium. The purpose of this research was to profile the application of physics learning using google classroom media at SMK Bodronoyo Jiwan, Madiun. The sample used was class X students majoring in APHP at SMK Bodronoyo Jiwan, Madiun. This research method is a descriptive qualitative data analysis model using the Technology Acceptance Model (TAM). The results of this research explain that the learning applied in class X APHP using google classroom gets a very good response. Obtaining this data states that on average students respond very satisfied, this is explained in 5 aspects, namely ease of access, perceived usefulness, communication and interaction, delivery of instructions, and student satisfaction on the application of Google Classroom in teaching and learning activities.